The Role of Istiwa' A'dzam as A Practical Verification of the Qibla Direction - Muhammad Syazwan Akmal Shahrizul; Muhammad Aqil Luqman Mohamed Khalid; Norazlina Subani (Kolej PERMATA Insan, 2025)
Insan Junior Researcher International Conference & Innovation (iJURECON) 2025 : “STREAM for a Better Future/ editor : Ahmad Fuad Mohamad Amin, Nurul Shazwani Binti Mohamed, Rossidi Bin Usop, Abdel Rahman Ibrahim Suleiman Islieh Organised by Kolej PERMATA Insan 10-11 October 2025